Біоекологічне обґрунтування фіторекультивації породних відвалів вугільних шахт Донбасу - Чайка, Микола Іванович; Chaika, Mykola Ivanovych (Харківський НАУ ім. В. В. Докучаєва, 2018)
У дисертаційній роботі біоекологічно обґрунтована і практично реалі-зована можливість фіторекультивації породних відвалів вугільних шахт Донбасу. Запропоновано оцінку екологічного аналізу фітоценотичної активнос-ті породних відвалів здійснювати методами ГІС інструментаріїв і дистан-ційного зондування адаптованими нами для техногенного екотопу. Встановлено низьке забезпечення рухомими формами поживних еле-ментів породи та наявність на кожному відвалі ділянок, токсичних для рос-лин за концентрацією водорозчинних солей. У досліджуваних видів най-більш поширеними типами тератологічних перетворень були гіпогенезія, дистонія кореневих систем, полімеризація пагонів і листків, олігомеризація пагонів і листків. Виявлено особливості впливу рослин і ґрунтових водорос-тей на вологість, температуру, актуальну кислотність, агрегатний склад по-роди і накопичення гумусу. Визначено видовий склад рослин породних відвалів, та флористичний і екоморфний аналіз структурної організації рослинного покриву техноген-них екотопів. Визначено ступінь представленості екобіоморф, питому ємність скла-ду екобіоморф, розподіл складу екобіоморф. Виділено типи розміщення екобіоморф на рослинних покривах поро-дних відвалів. Визначено видовий склад ґрунтових водоростей породних відвалів ву-гільних шахт. Розроблено ефективну технологію фіто рекультивації породних відва-лів, технічну структуру яких становлять біологічні пояси «Реви-Кондратюка». The intensive development of industry in Ukraine, together with the positive effect, leads to adverse consequences, manifestation of which is ecological problems. Donbass differs in especially high level of anthropogeogenesis in destabilization of stability of natural complexes. One of the main sources of this influence is mining of minerals. Only in the territory of Donetsk region is exploited about 300 deposits, and almost 2000 industrial enterprises of mining industry are concentrated, besides, almost 52% of the waste dumps of the coal mines and concentrating factories are located. High concentration of the enterprises and development of new territories by industry, increases onslaught of anthropogenic impact on nature, causes formation of man-made landscapes in Donbass, or their modifications. That is why the most urgent issues in the region are: to reduce emissions of pollutants from the coal industry into the atmosphere, soils and groundwater; to prevent the impact of anthropogenic pressure on land resources and natural objects; to ensure the conservation of rare species of plants and species that disappear; to create a holistic system for protection of natural objects. In solving these issues, recultivation of the disturbed lands and optimization of vegetation cover on such objects as the biological stage – phytorecultivation. The theoretical basis for solving these problems give the survey of phytorecultivation objects and the analysis of the received information in accordance with the form of SSTU 3008, conducting laboratory and field studies with the aim of identifying the mechanisms of abiotic and biotic self-purification processes, studying the ecological features of algal groups formation and the peculiarities of structural organization of vegetation on the waste dumps. The analysis of the legal documents allowed to establish: despite the fact that in Ukraine’s legislation as to protection of the environment, various levels of pollution by the industrial enterprises and human production activities were adopted by a number of laws and regulations of the government, in Donbas strong anthropogenic impact has led to changes in the primary landscapes, and somewhere to their complete replacement by anthropogenic. It is suggested that during the study of the characteristics of the objects, assessment of the ecological analysis of phytocoenic activity of the waste dumps to be carried out by GIS methods of instrumentation and remote sensing adapted by us for the technogenicecotope. The characteristic of the horizons morphology of the rock profile of the waste dumps is given. The following regularities are established: soil profile of low power, morphological differentiation of soils is poorly expressed; the differentiation of young soils morphologically occurs through the formation of a system of specific organogenic horizons. In the distribution of granulometric fractions of a rock in the layer 0–20 cm, the potential increase of the portion of small fractions was found with the age of the dumps, but the share of silt fraction remains not high and does not exceed 1%. It is established, the process of aggregation in the waste coal dumps takes place on the principles of zonal soils, but in the environment of poorly provided with organic substances. It is determined, the specific surface of the rock in the horizon 0–20 cm grows from top to bottom of the dump. It is established, low maintenance of moving forms of nutrient elements of the breed and the presence on each dump of the sites which are toxic to plants by concentration of water-soluble salts. The excess of the MPC amount, the content of moving forms of heavy metals in the waste dumps is determined beyond the integral index. It was found out in the ecotopes of the coal mines dumps, in the studied species the most common types of teratological transformations were hypogenesis, dystonia of root systems, polymerization of shoots and leaves, oligomerization of shoots and leaves. The peculiarities of influence of plants and soil algae on humidity, temperature, actual acidity, aggregate composition of the rock and accumulation of humus are revealed. Specific composition of plants of the waste dumps is determined. The floristic and ecomorphic analysis of the structural organization of the plant cover of anthropogenicecotops is made. The ecological and biological characteristic of root systems of plants on the rock dumps is presented. The division of the types according to the coenobitic types of their strategies is made. The indicators of productivity coefficient, ground (with fraction distribution) and underground phytomasses of micro groups from the waste dumps are presented. The degree of representation of the eco-biomorph, the specific capacity of the eco-biomorph composition, and the distribution of the eco-biomorph composition are determined. The eco-biomorphic organization of the vegetation cover of the waste dumps in the coal mines is presented. The types of eco-biomorphic placement on plant cover of the waste dumps are distinguished. The species composition of soil algae of the waste dumps of the coal mines is determined. An increase in the proportion of blue and green algae in the old waste dumpsis established. It is determined that the largest spectrum of algae species is concentrated in the horizon of 0-5 cm on rock fractions with a size of parts of 3–5 mm, 5–7 mm and 7–10 mm. Effective technological techniques of phytochemical treatment are developed, the technical structure of which consists of the biological zones of "Revi-Kondratiuk".
BioecologicalSubstantiation of Phytorecultivation of the Waste Dumps of Donbas Coal Mines
Keywords: біологічні пояси «Реви-Кондратюка»; biolohichni poiasy «Revy-Kondratiuka»; породний відвал; porodnyi vidval; рослинний покрив; roslynnyi pokryv; ступінь представленості екобіоморф; stupin predstavlenosti ekobiomorf; грунтові водорості; hruntovi vodorosti; фіторекультивація; fitorekultyvatsiia